EFFECTIVENESS OF EDUCAPLAY GAME-BASED LEARNING WITH THE CTL APPROACH TO IMPROVE STUDENTS’ MATHEMATICAL COMMUNICATION SKILLS - Diah Ayu Permata Sari; Bambang Sri Anggoro; Rosida Rakhmawati Muhammad (EMTEKA: Jurnal Pendidikan Matematika, 2026)
This study was conducted to address the low level of students’ mathematical communication skills in learning mathematics. It aimed to develop a game-based mathematics learning media using Educaplay integrated with the Contextual Teaching and Learning (CTL) approach to improve students’ mathematical communication skills on relations and functions material. The research was carried out at a junior high school involving 28 eighth-grade students. This study employed a Research and Development (R&D) method using the ADDIE model. Data were collected through expert validation sheets, student response questionnaires, and mathematical communication skill tests (pre-test and post-test).The results showed that the developed media was valid and feasible to use. The effectiveness test indicated an I ncrease in students’ average score from 51.92 in the pre-test to 76.82 in the post-test, with an N-Gain score of 0.56 (moderate category). This improvement reflects a moderate increase in students’ mathematical communication skills, particularly in visual representation and mathematical expression indicators. However, the improvement in written communication skills was relatively lower.These findings suggest that Educaplay-based learning media with the CTL approach is effective in improving students’ mathematical communication skills, although further development is needed to optimize written communication aspects. Penelitian ini dilatarbelakangi oleh rendahnya kemampuan komunikasi matematis peserta didik dalam pembelajaran matematika. Penelitian ini bertujuan untuk mengembangkan media pembelajaran matematika berbasis game Educaplay yang terintegrasi dengan pendekatan Contextual Teaching and Learning (CTL) guna meningkatkan kemampuan komunikasi matematis peserta didik pada materi relasi dan fungsi. Penelitian dilaksanakan di salah satu SMP dengan melibatkan 28 peserta didik kelas VIII. Metode yang digunakan adalah Research and Development (R&D) dengan model ADDIE. Teknik pengumpulan data meliputi lembar validasi ahli, angket respons peserta didik, serta tes kemampuan komunikasi matematis (pre-test dan post-test). Hasil penelitian menunjukkan bahwa media yang dikembangkan dinyatakan valid dan layak digunakan. Uji efektivitas menunjukkan adanya peningkatan rata-rata nilai peserta didik dari 51,92 pada pre-test menjadi 76,82 pada post-test dengan nilai N-Gain sebesar 0,56 yang termasuk kategori sedang. Peningkatan tersebut menunjukkan adanya peningkatan kemampuan komunikasi matematis peserta didik pada kategori sedang, terutama pada indikator representasi visual dan ekspresi matematis. Namun, peningkatan pada aspek komunikasi tertulis masih relatif lebih rendah. Dengan demikian, media pembelajaran berbasis Educaplay dengan pendekatan Contextual Teaching and Learning (CTL) cukup efektif dalam meningkatkan kemampuan komunikasi matematis peserta didik, meskipun masih diperlukan pengembangan lebih lanjut untuk mengoptimalkan aspek komunikasi tertulis.